Impact of Decadal Trends in the Surface Climate of the North Atlantic Subpolar Gyre on the Marine Environment of the Barents Sea - Koul, Vimal; Brune, Sebastian; Baehr, Johanna; Schrum, Corinna (Frontiers in Marine Science, 2022)
The Barents Sea is a key region in the Earth System and is home to highly productive marine resources. An integrated approach for strategic sustainable management of marine resources in such shelf-sea marine ecosystems requires, among many other aspects, a robust understanding of the impact of climate on local oceanic conditions. Here, using a combined observational and modelling approach, we show that decadal climatic trends associated with the North Atlantic Subpolar Gyre (SPG), within the period 1960-2019, have an impact on oceanic conditions in the Barents Sea. We relate hydrographic conditions in the Barents Sea to the decadal variability of the SPG through its impact on the Atlantic Inflow via the Faroe-Shetland Channel (FSC) and the Barents Sea Opening (BSO). When the SPG warms, an increase in the throughput of subtropical waters across the Greenland-Scotland Ridge is followed by an increase in the volume of Atlantic Water entering the Barents Sea. These changes are reflected in pronounced decadal trends in the sea-ice concentration and primary production in the Barents Sea, which follow the SPG after an advective delay of 4-5 years. This impact of the SPG on sea-ice and primary production provides a dynamical explanation of the recently reported 7-year lagged statistical relationship between SPG and cod {Gadus morhua) biomass in the Barents Sea. Overall, these results highlight a potential for decadal ecosystem predictions in the Barents Sea.